Pengaruh Public Relations dan Brand Image terhadap Intensi Membeli (Kasus: J.Co Donuts & Coffee) - Loudia Levina; Chairy - (Jurnal Manajemen Maranatha, 2013)
The purpose of this research is to investigate the influence of public relations activity and brand image on intention to buy, the case of J.CO Donnut & Coffe. The population of this study is students of Tarumanagara University who are also consumers of this brand. Sample was drawn using convenience samplingmethod. Hypothesis was tested using regression analysis. The research result showed that public relation as well as brand image influence intention to buy positively and significantly.